The effect of temperature on ferulic acid production by Aspergillus fumigatus (F01) from sago bark for generating biovanillin - Fatin Saiyidah, Ahmad Nordin (Universiti Malaysia Sarawak (UNIMAS), 2015)
Vanilla (4-Hydroxy-3-methoxybenzaldehyde) most commonly used as food flavouring agents. The demand for natural vanillin especially the amount of natural vanillin available that extracted from the vanillin pods is high. This has led to the investigation of alternative ways for the production of this flavour such as the biotechnological production from microorganisms known as biovanillin. Biovanillin can be produced by using different sources of microorganism including Aspergillus fumigatus. To produce biovanillin, ferulic acid (FA) was used as vanillin precursor. Therefore, the aim of the study is to produce FA from A. fumigatus. This was done via solid state fermentation (SSF) by using sago bark as substrate. Different range of temperature (30°C-40°C) that effects the FA production was studied. From this experiment it is found that the optimal temperature to produce high FA production was at 3SOC with duration of 10 days of incubation time. The amount of FA produced was 0.8812 mglg with 0.2643 U/g amount offerulic acid esterase (FAe) activity.